Anisotropic gravastar as horizonless regular black hole spacetime and its images illuminated by thin accretion disk - M. F. Fauzi; H. S. Ramadhan; A. Sulaksono (European Physical Journal C: Particles and Fields)
Abstract A connection between regular black holes and horizonless ultracompact objects was proposed in Carballo-Rubio et al. (JHEP 08:046, 2023, arXiv:2211.05817 [gr-qc]). In this paper, we construct a model of a horizonless compact object, specifically an anisotropic gravastar with continuous pressure, that corresponds to regular black hole spacetime in the appropriate limit. The construction begins by modeling an equation of state that satisfies the anisotropic gravastar conditions and transitions to the de Sitter ( $$p=-ε $$ p = - ϵ ) upon horizon formation. The spacetime structure is similar to the Quantum Horizonless Compact Object (QHCO) described in Chen and Yokokura (Phys Rev D 109:104058, 2024, arXiv:2403.09388 [gr-qc]). Within this model, we also generate images of the corresponding objects surrounded by a thin accretion disk. The resulting images reveal that assuming that the emitting matter exists only outside the object, the inner light ring structure closely resembles that of the horizonless configuration of a regular black hole and the QHCO, yet it exhibits a distinct light ring structure compared to the thin-shell gravastar model. However, the opposite occurs when emitting matter is taken into account inside the object.